2003
DOI: 10.1556/aagr.51.2003.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal non-adapted arbuscular mycorrhizal fungi on Cd, Ni and Zn uptake by ryegrass

Abstract: The aim of the present study was to observe the effect of metal non-adapted arbuscular mycorrhizal fungi (AMF) application on the metal uptake of the host plant in a pot experiment. The soil samples originated from a calcareous chernozem soil treated with Cd, Ni and Zn with ryegrass (Lolium perenne L.) as the test plant. Changes in the parameters of mycorrhizal root colonization and in the metal uptake of the host as affected by metal type, metal rate and mycorrhizal treatments were investigated. efficient myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Similar results were found in another experiment with ryegrass in which metal concentrations were 0, 30, 90, and 270 mg kg À1 . The presence of AMF was correlated with higher Zn content in the root, preventing Zn from penetrating the shoot, and thereby reduced the effects of metal toxicity (Taka´cs and Vo¨ro¨s 2003). For maize, concentrations of Zn were lower in mycorrhizal plants than in non-inoculated plants (Weissernhorn et al 1995).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar results were found in another experiment with ryegrass in which metal concentrations were 0, 30, 90, and 270 mg kg À1 . The presence of AMF was correlated with higher Zn content in the root, preventing Zn from penetrating the shoot, and thereby reduced the effects of metal toxicity (Taka´cs and Vo¨ro¨s 2003). For maize, concentrations of Zn were lower in mycorrhizal plants than in non-inoculated plants (Weissernhorn et al 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Zn contamination may reduce (Bi et al 2003;Taka´cs and Vo¨ro¨s 2003) or enhance (Zhu et al 2001) AMF colonization or have no effect . Chen et al (2001) demonstrated that the concentration of Zn in AM fungal mycelia is approximately ten times higher than in the host plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings with non-adapted fungi have also shown the potential applicability of symbiosis in other methods of phytoremediation, such as phytoextraction (Takács and Vörös, 2003).…”
Section: Microbial Biomass In Phytoremediationmentioning
confidence: 88%
“…Mivel nagy mennyiségben és sok területen használják ezeket a nanoszemcsés fém-oxidokat a talajok a kezelésére is, így célszerű ezekkel az anyagokkal foglalkozni a talajbióta stresszválaszainak vizsgálata során. A különböző nehézfémek hatásait talajmikrobákra több magyar kutató is vizsgálta (VÖRÖS et al, 1998;TAKÁCS & VÖRÖS 2003;BIRÓ et al, 2005;SZÉCSY et al, 2011), viszont a nanoméretű fém-oxidokra jóval kevesebb vizsgálat született (KISS et al, 2015). Alkalmazásukból eredően a talaj élővilága számára környezeti kockázatot jelentő fém-oxidok: a szilí-cium-dioxid (SiO 2 ), a titán-dioxid (TiO 2 ), az alumínium-oxid (Al 2 O 3 ), a cérium-oxid (CeO 2 ), a vas-oxid (Fe 2 O 3 vagy Fe 3 O 4 ), a cink-oxid (ZnO) és a réz-oxid (CuO).…”
Section: A Nanotechnológia Napjainkbanunclassified